Incidence and risk factors of surgical site infection in a tertiary health institution in Kano, Northwestern Nigeria - Nwankwo, Emmanuel Onwubiko; Ibeh, Isaiah; Enabulele, O I (International Journal of Infection Control, 2012)
Surgical site infection (SSI) is the most common complication following surgical procedures. The aim of this study was to determine the incidence and associated risk factors of surgical site infection in a tertiary health institution in Kano, Nigeria. The study was carried out between January 2008 and December 2010 at Aminu Kano Teaching Hospital, Kano. Data was collected in a predesigned questionnaire forms which focused on demographic details, socioeconomic background and lifestyle while the diagnosis, surgical procedure, duration of surgery, prophylactic antibiotics, postoperative antibiotics and co-morbidity were obtained from the patients hospital records. All the patients who underwent surgery in the male and female surgical wards, gyneacology and maternity wards including paediatric wards were enrolled in the study after informed consent or parents in the case of children. All patients were followed up for 30days for development of surgical site infection. Infected cases were identified using CDC, USA definition for surgical site infections. Out of 2880 patients, 585 (20.3%) were confirmed to be clinically infected. There were 1,016 (35.3%) males mean age 38.3±16.3 and 1864 females (64.9%) mean age 30.6 ± 12.3yrs. There were 65% Superficial Incisional SSI, 30% deep Incisional SSI and 5% Organ Space SSI. Incidence related to clean, clean contaminated, contaminated and dirty were 5.8%, 30.5%, 40.6%, and 64.8% wounds respectively. Age, anaemia, obesity, number in operating room and duration of surgery were all significantly associated with surgical site infection. Effective infection control measures and good regular surveillance will improve the SSI rate to an acceptable level.